Impact of right ventricular work and pulmonary arterial compliance on peak exercise oxygen uptake in idiopathic pulmonary arterial hypertension. (15th May 2021) - Messina, Carolina M.S.; Ferreira, Eloara V.M.; Singh, Inderjit; Fonseca, Angelo X.C.; Ramos, Roberta P.; Nery, Luiz E.; Systrom, David M.; Oliveira, Rudolf K.F.; Ota-Arakaki, Jaquelina S.
Abstract: Background: Pulmonary arterial hypertension (PAH) is associated with increased right ventricular (RV) afterload, RV dysfunction and decreased peak oxygen uptake (pVO2 ). However, the pulmonary hemodynamic mechanisms measured by exercise right heart catheterization (RHC) that contribute to reduced pVO2 in idiopathic PAH (IPAH) are not completely characterized. Therefore, we sought to evaluate the exercise RHC determinants of pVO2 in patients with IPAH. Methods: 519 consecutive patients with suspected and/or confirmed pulmonary hypertension were prospectively screened to identify 20 patients with IPAH. All IPAH patients were prospectively evaluated with resting and exercise RHC and cardiopulmonary exercise testing. Results: 85% of the patients were female; the median age was 34[29–42] years old. At peak exercise, mean pulmonary arterial (PA) pressure was 76 ± 17 mmHg, PA wedge pressure was 14 ± 5 mmHg, cardiac output (CO) was 5.7 ± 1.9 L/min, pulmonary vascular resistance was 959 ± 401 dynes/s/cm 5 and PA compliance was 0.9[0.6–1.2] ml/mmHg. On univariate analysis, pVO2 positively correlated to peak CO, peak cardiac index, peak stroke volume index, peak RV stroke work index (RVSWI) and peak oxygen saturation. There was a negative correlation between pVO2 and Δ (rest to peak change) PA compliance. In age-adjusted multivariate model, peak RVSWI (Coefficient = 0.15, Beta = 0.63, 95% CI [0.07–0.22], p < 0.01) and ΔPA compliance (Coefficient = −2.51, Beta = −0.43, 95% CI [−4.34-(−0.68)], p = 0.01) had the best performance predicting pVO2 (R 2 = 0.66). Conclusions: In conclusion, a load dependent measurement of RV function (RVSWI) and the pulsatile component of RV afterload (ΔPA compliance) significantly influence pVO2 in IPAH, further highlighting the pivotal role of hemodynamic coupling to IPAH exercise capacity. Highlights: The dynamic interplay between pulmonary vascular reserve, RV performance and pVO2 remains incompletely characterized in idiopathic PAH. Reduced pulmonary vascular reserve and decreased exercise RV work impact pVO2 in idiopathic PAH. The findings point to the central role of load dependent measures of RV function and pulsatile RV afterload to idiopathic PAH exercise capacity. The findings further highlight the pivotal role of hemodynamic coupling in determining exercise capacity in idiopathic PAH patients.